THE STATE OF UKRAINE'S FOOD SECURITY IN CONDITIONS OF UNCERTAINTY - PODSOKHA, Anna; PRUSOVA, Galina; CHUB, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on the state of food security in Ukraine under conditions of uncertainty.It is established that food security in Ukraine remains highly complex and at the same time dynamic, since the full-scale war has significantly destabilized all key links in the agri-food chain (from growing crops to storage, processing, transportation, and export). The occupation of fertile territories, mining of fields, lack of resources, and large-scale destruction of infrastructure have significantly limited the agricultural sector's ability to meet both domestic needs and fulfill international contracts.It has been proven that the economic crisis, caused by both the war and global market fluctuations, has deepened inequality in access to food resources, particularly among vulnerable social groups and in the affected regions. A significant increase in prices for food, fuel, and agrochemicals has created an additional burden on households, primarily in combat zones and among internally displaced persons.It is determined that despite all the challenges, the Ukrainian agri-food system demonstrates the ability to adapt and resist. Farmers, state institutions, and international organizations are actively seeking new approaches, including alternative logistics, production modernization, humanitarian initiatives, demining programs, and sectoral recovery. This suggests the presence of internal potential for transformation and development, even in the most challenging conditions.It is substantiated that the current state of food security in Ukraine can be characterized as a crisis. However, it is not a hopeless one, since within the existing framework of instability, the foundations are already being laid for a more sustainable, adaptive, and sovereign agri-food policy in the future.
Keywords: agricultural products; challenges; economic instability; export of products; inflation; logistics; food security; world market; social disparities